Numerical Modeling of Coupled Surge-Heave Sloshing in a Rectangular Tank with Baffles - Lv Ren; Yinjie Zou; Jinbo Tang; Xin Jin; Dengsong Li; Mingming Liu (Shock and Vibration)
Liquid sloshing under coupled surge and heave excitations in a rectangular tank has been numerically investigated by applying a Navier–Stokes solver. Fieriest coupled sloshing was further considered, and the internal baffle was expected to suppress the violent sloshing wave. After getting fully validated against available results from the literatures, the numerical model was applied to research coupled sloshing, and both vertical baffle and horizontal baffle have been considered. Due to the strong vortexes created by the sharper corners of the baffles and the reduction of the effective water bulk climbing through the tank walls, the sloshing was dramatically reduced. The increase of the baffle distance away from the tank bottom led to a decrease in the sloshing wave. It was noted that the baffle near the free surface caused the maximal dissipation. The frequency response of the sloshing wave was accordingly illustrated.